An Ethnoludography of the Game Design Industry in Kathmandu, Nepal - Grieve, Gregory P. (Gamevironments, 2018)
What counts as the field site when researching Nepali video game developers? Concentrating on the company Arcube Games and Animation, in the summer of 2017 I used the ethnoludographic method to research game development in the Kathmandu Valley. I recorded my findings in field notes, photographs, written documents and other material culture. My usual ethnographic method developed in two ways. First, I engaged in ludography, a humanistic qualitative method for interpreting gaming. Second, Nepal proved not to be an isolated location, but rather a vortex of global flows. I found that in the Kathmandu valley these flows are often focused on a fantasy of Shangri-La that poses Nepal as an underdeveloped traditional nation, full of picturesque poverty, and over-determined with religious culture, but blessed with beautiful Himalayan landscapes.
Accepted: 2020-03-25T23:30:09Z
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé